Extranodal Natural-Killer/T-Cell Lymphoma, Nasal Type - Harinder Gill; Raymond H. S. Liang; Eric Tse (Advances in Hematology)
The World Health Organization (WHO) classification recognizes 2 main categories of natural killer (NK) cell-derived neoplasms, namely, extranodal NK/T-cell lymphoma, nasal type, and aggressive NK-cell leukaemia. Extranodal nasal NK/T-cell lymphoma is more frequent in the Far East and Latin America. Histopathological and immunophenotypical hallmarks include angiocentricity, angiodestruction, expression of cytoplasmic CD3 epsilon (ε), CD56, and cytotoxic molecules and evidence of Epstein-Barr virus (EBV) infection. Early stage disease, in particular for localized lesion in the nasal region, is treated with chemotherapy and involved-field radiotherapy. On the other hand, multiagent chemotherapy is the mainstay of treatment for advanced or disseminated disease. L-asparaginase-containing regimens have shown promise in treating this condition. The role of autologous hematopoietic stem cell transplantation is yet to be clearly defined. Allogeneic hematopoietic stem cell transplantation, with the putative graft-versus-lymphoma effect, offers a potentially curative option in patients with advanced disease.